Growth and survival in relation to various stocking densities of catla (Catla catla Ham.) spawn fed on a dry artificial diet - Swain, S K; Mohanty, S N; Tripathi, S D (Indian Journal of Fisheries, 2011)
Catla spawn weighing 1.5 mg were reared in the laboratory on a dry artificialdiet containing 50 % goat liver, 30 % bioboost forte, 13 % starch, 5 % cod liveroil, 1 % each vitamin and mineral mixtures at 28-29Â°C for 21 days at threestocking densities of 60, 80 and 100 million/ha. Spawn reared at 60 millionyha showed the maximum average weight of 67 mg with 87 % survival, thegrowth and survival rates decreased with increasing stocking densities. Theaverage weight and survival of spawn reared in 80 and 100 million/ha were38 mg & 69 % and 30 mg & 68 % respectively